The Development of Integration Theories in Hungary - Pallai, László (The Development of European and Regional Integration Theories in Central European Countries, 2022)
Since the turn of the 18th and 19th centuries, the idea of integration has been on the agenda in Hungary, as well as in Central and Eastern Europe. It materialized in the formulation of various federation and confederation plans. Even though these ideas were generally far removed from political reality and therefore, had little chance of being realized, they were nevertheless reformulated. In the 19th century, the federation ideas of the Habsburg Empire were dominant, which also meant preserving the territorial unity of historic Hungary. Between the two world wars, the most influential and resonant ideas were those of the Pan-European movement and those from the Germans in various forms of Mitteleuropa. After the Second World War, Soviet-style forms of integration prevailed. Following the political transitions, the so-called Visegrad concept gained new momentum and is now dominant in the region. KEYWORDS: federation, confederation, Hungarian integration ideas, Habsburg Empire federalization, Mitteleuropa plans, Pan-European Movement, socialist integration, Comecon, Visegrad concept